JTT-130, a Novel Intestine-Specific Inhibitor of Microsomal Triglyceride Transfer Protein, Improves Hyperglycemia and Dyslipidemia Independent of Suppression of Food Intake in Diabetic Rats. (7th May 2014) - Sakata, Shohei; Ito, Makoto; Mera, Yasuko; Sasase, Tomohiko; Yamamoto, Hiromi; Kakutani, Makoto; Ohta, Takeshi
Abstract : We investigated the effects of JTT-130 on glucose and lipid metabolism independent of the suppression of feeding by comparing with pair-fed animals. Male Zucker diabetic fatty (ZDF) rats were divided into control, JTT-130 treatment, and pair-fed groups. The rats were fed with a regular powdered diet with or without JTT-130 as a food admixture for 6 weeks. We compared the effects on glucose and lipid metabolism in JTT-130 treatment group with those in pair-fed group. Results . Hyperglycemia in ZDF rats was prevented in both JTT-130 treatment and pair-fed groups, but the prevention in pair-fed group became poor with time. Moreover, reduction in plasma cholesterol levels was observed only in JTT-130 treatment group. JTT-130 treatment group showed improved glucose tolerance at 5 weeks after treatment and significant elevation of portal glucagon-like peptide-1 (GLP-1) levels. The hepatic lipid content in JTT-130 treatment group was decreased as compared with pair-fed group. Furthermore, pancreatic protection effects, such as an increase in pancreatic weight and an elevation of insulin-positive area in islets, were observed after JTT-130 treatment. Conclusions . JTT-130 improves hyperglycemia and dyslipidemia via a mechanism independent of suppression of food intake, which is ascribed to an enhancement of GLP-1 secretion and a reduction of lipotoxicity.